Sisingaan Art as a Vehicle for Digital Civic Culture: A Netnographic Analysis of the Internalization of Local Wisdom Values ​​in Generation Z - Aini, Dinda Nurul (Universitas Sultan Ageng Tirtayasa, 2026)
The shift in the cultural landscape from physical to digital spaces has created a new arena for the expression and internalization of local wisdom values. This article aims to analyze how Sisingaan art from Subang Regency, West Java, has transformed into a vehicle for digital civic culture among Generation Z. This phenomenon is highly relevant to examine because it reflects the recontextualization of traditional arts that have not simply migrated to the online ecosystem but have also undergone an adaptive shift in meaning. Using netnographic research methods, this study examines the content and patterns of online interactions related to Sisingaan on the social media platforms TikTok and Instagram. The research instruments used include digital field notes, observation guides, coding matrices, and in-depth literature studies. The research findings indicate that Sisingaan in the digital world has become a substantial space for identity negotiation. Through thematic analysis of video content, creative narratives, and interactions in the comment section, it is identified that fundamental values ​​such as social solidarity, cultural resilience, and historical awareness have been successfully internalized among Generation Z. This article provides a theoretical contribution to understanding the dynamics of civic culture in the digital era. The results of this study confirm that the preservation of local wisdom requires narrative adaptation that is relevant to the digital character of Generation Z, while also providing strategic implications for the formulation of sustainable cultural policies in the future.